2021
DOI: 10.1002/adfm.202105164
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Quasi‐2D Perovskite into 3D Perovskite Using Formamidine Acetate Additive for Efficient Blue Light‐Emitting Diodes

Abstract: Perovskite films have emerged as candidates for light‐emitting diodes on accounts of excellent optical properties and low cost. Construction of quasi‐2D perovskite films by incorporating organic ammonium is an effective method to manufacture a pinhole‐free film with high photoluminescence quantum yield (PLQY). However, excess organic ammonium hampers carrier mobility through forming insulating capping layer and facilitates the formation of alow‐dimensional perovskite (n = 1 and n = 2) phase that accelerates no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 47 publications
(44 reference statements)
1
25
0
Order By: Relevance
“…We further examined the passivation of l -TrpBr in the performances of quasi-2D PeLEDs. Figure c shows that the turn-on voltage ( V on ) is reduced from 2.8 to 2.6 V, and the maximum luminance increased from 11 827 to 37 785 cd m –2 after introducing l -TrpBr, confirming that the defects in quasi-2D perovskite films were suppressed by l -TrpBr . Furthermore, the peak EQE of the champion device reaches 14.32% at 1526 cd m –2 at a current density of 3.17 mA cm –2 (Figure d).…”
mentioning
confidence: 70%
“…We further examined the passivation of l -TrpBr in the performances of quasi-2D PeLEDs. Figure c shows that the turn-on voltage ( V on ) is reduced from 2.8 to 2.6 V, and the maximum luminance increased from 11 827 to 37 785 cd m –2 after introducing l -TrpBr, confirming that the defects in quasi-2D perovskite films were suppressed by l -TrpBr . Furthermore, the peak EQE of the champion device reaches 14.32% at 1526 cd m –2 at a current density of 3.17 mA cm –2 (Figure d).…”
mentioning
confidence: 70%
“…Preparation of the Precursors: Cs 2 CO 3 , FA(Ac), and Na 2 CO 3 were dissolved in OTAc with the molar concentration of 0.1, 0. , and 0.1 m as Cs-solution, Ac-solution (FA + cation is selected as the cation regarding the stability of the lattice [38] ), and OTAc-solution, respectively. During the dissolution process, the CO 3 2− will become CO 2 and generate octoate.…”
Section: Methodsmentioning
confidence: 99%
“…[35] Based on this research conclusion, it has also been reported that a low exciton binding energy, which represents the weak quantum confinement effect, is beneficial to improving the photoelectric properties of 2D perovskites. [36,37] According to the fitting results of temperature-dependent PL measurements above, the smaller E b value of the target perovskite film indicated the reduced confinement effect, which was more conducive to carrier injection and transfer. To further test our conjecture, hole-only (Figure 3e) and electron-only (Figure 3f) devices with the structure of ITO/PVK/perovskite/MoO 3 /Ag and ITO/SnO 2 /perovskite/PO-T2T/Liq/Al respectively were constructed.…”
Section: T I Aementioning
confidence: 98%